APIs and Libraries. Issue 4 (1st October 2016) - Davis, Robin Camille
Abstract: This column introduces application programming interfaces (APIs) and discusses how APIs are used in various library projects. APIs allow developers to use and reuse information in new ways and on a larger scale. In the landscape of digital libraries, APIs are enabling exciting new endeavors and simplifying routine tasks. Included is a table of library-related APIs from organizations such as OCLC, Ex Libris, and the New York Public Library.